Pengaruh Media Sosial dengan Konten Hoak/Bohong/Fitnah dan Aspek Psikologi Hukumnya terhadap Keluarga - Najib, Afifun Najib (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
This study examines the influence of social media with hoax/lie/slander content and its legal psychology aspects on families with a psychological approach. This study is a normative-explanatory study, namely examining, explaining, and explaining descriptively qualitatively with a psychological approach. Data were obtained through literature studies. The analysis was carried out by examining how strong the influence of social media with hoax/lie/slander content and its legal psychology aspects is on the life of a family. The research findings show that social media with hoax/lie/slander content is considered as something that has negative potential and can cause harm, disrupting family stability. Meanwhile, the legal psychology aspect towards the family has a legal psychology impact towards the family that can be caused: fading trust in each other from the family members who make hoaxes which can affect the psychological stability of the person concerned, then family disintegration which leads to the breaking of the bonds of brotherhood so that it affects the health of psychological relationships between family members, which are increasingly strained and will gradually be completely broken and kinship becomes alien which results in the absence of a sense of mutual care and affection between family members and can lead to psychological shocks which have a bad impact.